Employee Voice Mechanisms, Voice Embeddedness, and Silence in Tax Professionals - Radya Brian Aurelio; Diana Puspitasari (Jurnal Inovasi Pajak Indonesia, 2025)
Purpose – Building on social exchange theory and emotional dissonance hypothesis, we draw overarching attention to how formality of employee voice mechanism shapes employee silence via perceived voice embeddedness, with the moderating role of power distance orientation in professional tax environment. Design/methodology/approach – The research is a quantitative survey design, performs the structural equation modeling and tests the moderated mediation model that intertwines MV mechanisms with embeddedness perceptions and cultural orientation. Findings – Results indicate the degree to which employee voice mechanisms uniformly eliminate silence. Their efficacy is contingent on whether employees believe that voice is actually embedded in organizational processes of decision making. Perceptual voice embednenss is central for those mechanisms of contact to be transformed into attenuated silence or pure symbolicity streamed from the speech chain. In addition, the hierarchical culture orientation attenuates the silence-mitigating effect of embedded voice, meaning that cultural context influences how employees react to formal voice channels. Originality/value – This study contributes to the employee voice literature by incorporating voice embeddedness as a crucial explanatory mechanism and by revealing its contingent effectiveness according to power distance orientation. It applies voice theory further to the professional tax contexts under-researched in previous studies. Research Implications – This finding underscores the need to look beyond the simple existence of voice mechanisms to how employees perceive their credibility and impact. The research highlights the necessity of combining institutional and cultural approaches to examine employee voice and silence in the future.